A Critical Appraisal of Product Innovation in Islamic Banking: Navigating Market Pressures, Ensuring Shariah Compliance, and Advancing the Objectives of Maqasid al-Shariah - Ismaulina; Azharsyah Ibrahim (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2025)
This article presents a critical evaluation of product innovation in Islamic banking, focusing on the imbalance between market demands, sharia compliance, and the realization of maqashid al-shariah. The study aims to assess the extent to which Islamic banking innovations can maintain a balanced integration of commercial objectives, legal-formal compliance, and the substantive values of maqashid. Employing a descriptive qualitative approach through case studies of several Islamic banks in Indonesia, the research gathers data from annual reports and strategic publications. Analysis is conducted using the Maqashid-Based Innovation Evaluation Model (MBIEM), which encompasses three core dimensions: market orientation, sharia compliance, and alignment with maqashid. Findings reveal a significant gap between formalistic compliance and the actual implementation of maqashid. Value-based innovations such as qardhul hasan financing and digital zakat platforms are found to better embody maqashid values than products driven solely by legal-formal considerations. The study recommends reinforcing maqashid-oriented regulations, involving the Sharia Supervisory Board (SSB) early in product development, enhancing the multidisciplinary competencies of human resources, and developing a substance-based sharia audit framework. With these strategies, Islamic banking innovations are expected to become more ethical, inclusive, and sustainable, while fulfilling their socio-economic role in accordance with Islamic principles